2004
DOI: 10.1097/00004872-200412000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new non-invasive portable tonometer for determining arterial pressure wave and pulse wave velocity

Abstract: These results show that the PulsePen enables an easy and reliable evaluation of central arterial pressure and stiffness in clinical ambulatory practice, especially in high-risk patients in whom arterial stiffness has been shown to be a significant indicator of morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
213
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(229 citation statements)
references
References 29 publications
6
213
0
10
Order By: Relevance
“…29 The applanation tonometry devices PP and SC are invasively validated. 12,27 Both use electrocardiogram-gated sequential tonometric measurements to asses aortic (carotid-femoral) PWV and are widely used in clinical and research practice. [23][24][25] Survival studies in adults indicate that PWV measured by applanation tonometry has a good clinical predictive value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 The applanation tonometry devices PP and SC are invasively validated. 12,27 Both use electrocardiogram-gated sequential tonometric measurements to asses aortic (carotid-femoral) PWV and are widely used in clinical and research practice. [23][24][25] Survival studies in adults indicate that PWV measured by applanation tonometry has a good clinical predictive value.…”
Section: Discussionmentioning
confidence: 99%
“…The pulse travel distance was defined as the difference between the distance from the carotid sampling site to the jugular notch and distance from the jugular notch to the femoral sampling site (Figure 1a). 27 The pulse wave was calibrated by measuring brachial blood pressure immediately before each recording. The measurement of pulse pressure was discarded and repeated if blood pressure and heart rate varied by more than 10% in the carotid and femoral sites.…”
Section: Devices Based On Applanation Tonometrymentioning
confidence: 99%
See 1 more Smart Citation
“…We used carotidfemoral PWV and CIMT as surrogate measures for structural and functional abnormality of the arterial wall as they have shown to be valid and reproducible methods that are simple and non-invasive. 22,23 A major concern in studies that relate the biomarkers to disease is confounding by a third variable through unknown mechanisms. Consistent with previous evidence, our finding showed that most of the established cardiovascular risk factors are determinants of aortic PWV and CIMT.…”
Section: Discussionmentioning
confidence: 99%
“…The PulsePen device has been previously described in details. [27][28] Herein, when the difference between heart rate recorded during the carotid measurement and that recorded during the femoral measurement was equal or greater than 10%, the PWV measurement was repeated (the difference in heart rate is indicated in the PulsePen software). According to this procedure, measurement of PWV had to be repeated in seven subjects.…”
Section: Reference Methodsmentioning
confidence: 99%